2005
DOI: 10.1182/blood.v106.11.3096.3096
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Gene Therapy of Graft-Versus-Host Disease Induced by Central Memory Human T Lymphocytes.

Abstract: Suicide gene therapy (SGT) is a powerful approach to exploit anti-host reactivity following allogeneic hemopoietic cell transplantation (allo-HCT) for a full graft-versus-leukemia (GvL) effect, while controlling graft-versus-host disease (GvHD). This is accomplished through genetic modification of donor lymphocytes with a suicide gene. The herpes simplex thymidine kinase (TK) suicide gene converts at a cellular level the pro-drug ganciclovir (GCV) into tri-phosphate toxic derivatives, thence conferring selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Clinical trials are underway. Preliminary trials describe the successful abrogation of GVHD by ganciclovir (Bondanza et al, 2006). One problem with the approach is the potential for damage to the T-cell repertoire during proliferation in culture necessary for Tk gene transfection.…”
Section: Suicide Gene Insertionmentioning
confidence: 99%
“…Clinical trials are underway. Preliminary trials describe the successful abrogation of GVHD by ganciclovir (Bondanza et al, 2006). One problem with the approach is the potential for damage to the T-cell repertoire during proliferation in culture necessary for Tk gene transfection.…”
Section: Suicide Gene Insertionmentioning
confidence: 99%
“…44 Addition of CD28 costimulation to CD3 activation helps to preserve the immune competence of the T cells. 45,46 Alternative suicide genes based on the dimerization of Fas 47 or caspase 9 48 in the apoptotic pathway have been developed to circumvent the problem of immunogenicity of HSV-tk.…”
Section: Recognition Of Target Antigens Independentmentioning
confidence: 99%
“…Depending on the clinical setting, gene transfer may target antigen-specific cells, using antigenspecific stimulation, 3 or polyclonal T cells, using mitogens or CD3 antibody-mediated activation. 4 We 5-7 and others [8][9][10][11][12][13][14] have shown both in vitro and in vivo, using murine and canine models of HSC transplantation, that T-cell expansion following stimulation with phytohaemaglutinin (PHA), CD3 or CD3/CD28 is associated with decreased alloreactivity. In particular, we reported that Summary CD3-and CD28-activated T cells expanded for 12 days ex vivo to produce suicide gene-modified T cells are hyporesponsive to alloantigens.…”
Section: Introductionmentioning
confidence: 99%
“…6 Assessments performed in murine GvHD models in vivo demonstrate that CD3/CD28 costimulation prevents alterations of the T-cell receptor Vb repertoire during ex vivo expansion 7,15 as well as decreases in Epstein-Barr virus (EBV) reactivity 16,17 and alloreactivity. 11,13 Thus, CD3/CD28 costimulation is preferred to CD3 or mitogen activation for producing GMC. 8,13,18 However, cells expanded with interleukin (IL)-2 after CD3/CD28 costimulation (Co CD3/CD28 cells) still have decreased alloreactivity when assessed in vitro in MLRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation